2010
DOI: 10.1016/j.jcmg.2009.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Vulnerable Coronary Plaques by Color Fluorescent Angioscopy

Abstract: Color fluorescent angioscopy provides objective information related to coronary plaque composition and may help identify unstable plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 12 publications
2
86
1
Order By: Relevance
“…23,24) In this study, red fluorescence was observed not only in the plaques but also in the apparently normal segments. This fact indicates that LPC deposits in the coronary wall independent of the deposition of other lipids.…”
Section: Discussionsupporting
confidence: 53%
“…23,24) In this study, red fluorescence was observed not only in the plaques but also in the apparently normal segments. This fact indicates that LPC deposits in the coronary wall independent of the deposition of other lipids.…”
Section: Discussionsupporting
confidence: 53%
“…2 In the present study, ceramide visualized by FM, ceramide stained by standard Ziel-Neelsen stain 8 and…”
Section: Role Of Macrophages In Ceramide Productionmentioning
confidence: 67%
“…In our preliminary and previous studies, collagen I exhibited blue fluorescence and a mixture of cholesterol or cholesteryl esters with collagen I and β-carotene exhibited a light-blue to white color ( Table 1). 8 It is conceivable that the failure to detect the Go of ceramide in plaque with a FC thicker than 100 µm was because of masking of the Go by these other substances.…”
Section: Masking Of Ceramide By the Fcmentioning
confidence: 99%
“…Recently, color fluorescent angioscopy has become available as an advanced modality. It can be used to visualize not only collagen fibers but also oxidized LDL, and can provide useful information related to the plaque composition (36). Among the reports with IVUS, Taguchi (40).…”
Section: Reduction Of Ldl Cholesterol and Modification Of Plaque Instmentioning
confidence: 99%